Hubungan Pemberian Ekstrak Jahe Merah (Zingiber Officinale Var.Rubrum) Terhadap Tekanan Darah Pada Ibu Lansia dengan Hipertensi Di Muslimat Nu Anak Cabang Bugul Kidul Kota Pasuruan - Yunietha Firdaus Safirah; Tut Rayani Aksohini Wijayanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Hypertension is a chronic disease that is often experienced by the elderly and is often called a silent killer because it often does not cause symptoms until it causes serious complications such as stroke, kidney failure, or heart attack. The purpose of this study was to see the impact of giving red ginger extract on reducing blood pressure in elderly mothers with hypertension. This study used a pre-experimental design with a one group pretest-posttest design pattern involving 32 elderly people with hypertension as samples, obtained through total sampling techniques. The intervention was carried out by giving 4 grams of red ginger extract per day for seven consecutive days. Testing was carried out using a paired t-test. The average value before the intervention was 1.9375, while after the intervention the average decreased to 1.5313. Statistical tests showed a significant difference between blood pressure before and after the intervention with a p value = 0.000 (p <0.05). Administration of red ginger extract has been proven effective in lowering blood pressure in elderly people with hypertension.